Pengembangan Buku Teks Peradaban Makanan Pokok Berbasis PjBL untuk Menumbuhkan Karakter Toleransi - Trisnawati, Putri Hidayah; Nugrahanta, Gregorius Ari (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The tolerance character crisis in children is concerning due to a lack of effective learning media. This study developed a PjBL-based textbook on staple food civilization using the ADDIE model to foster tolerance. Data were collected through tests, analyzed quantitatively and qualitatively, and implemented with eight children aged 10-11 in a Purworejo elementary school. Results showed the textbook was of “very good” quality (score 3.78) and highly effective (98,87%) in fostering tolerance, reflected in positive behavioral changes aligned with tolerance indicators in the children’s daily lives.